Improving the diversification of herbal pastries and digital marketing applications to increase product sales - Agus Setiyoko; Rani Dwi Lestari; Ika Wulandari (University of Merdeka Malang, 2023)
Members of KWT Sewagati Pasekan Lor encountered difficulties as a result of their lack of knowledge and expertise about the diversification of various processed herbal pastries, food labeling and packaging technology, and digital-based product marketing. This volunteering project aims to improve members' knowledge and abilities in relation to the variety of processed herbal pastries, label and packaging technology, and digital-based marketing. The community service method used is counseling which includes theories regarding the diversification of processed herbal pastries, brands, and types of packaging, as well as digital-based marketing practices. The counseling continued with making herbal pastries such as turmeric cakes, cinnamon egg rolls, and ginger nastar. The training on labeling and packaging as well as digital-based marketing practices. The outcomes of this community service project demonstrate that the Partner's knowledge about the variety of processed herbal pastries increased from 50% to 90%, the partner's skills in processing various herbal pastries rose from 55% to 80%, the capacity for comprehending and creating labels and food packaging also improved from 45% to 80% and knowledge and skills in digital marketing increased from 40% to 75%.